The weak min-max property in Banach spaces - Ouyang, Zhengyong; Rasila, Antti; Guan, Tiantian (MATHEMATICA SCANDINAVICA, 2022)
In this paper, we investigate the relationship between the weak min-max property and the diameter uniformity of domains in Banach spaces with dimension at least 2. As an application, we show that diameter uniform domains are invariant under relatively quasimöbius mappings.